Development of Loop-Mediated Isothermal Amplification Combined with Lateral Flow Dipstick Assay for a Rapid and Sensitive Detection of Cystic Echinococcosis in Livestock in Kenya. (27th February 2022) - Badoul, Nasser Arreh; Kagira, John; Ng'ong'a, Florence; Dinka, Hunduma
Abstract : Background . Cystic echinococcosis is a zoonotic disease caused by the metacestode stage of Echinococcus granulosus and occurs worldwide, causing considerable economic losses and public health problems. The currently available methods for the diagnosis of animal hydatidosis are time-consuming and require well-equipped laboratories which make them incompatible with testing in resource-poor settings. This study developed and evaluated a rapid, more sensitive, and specific loop-mediated isothermal amplification combined with a lateral flow dipstick assay for the rapid and sensitive detection of cystic echinococcosis. Results . In this study, a specific primer set and FITC-labeled probe targeting the conserved region of the NADH-1 gene were designed. The LAMP reaction was performed at 60°C for 40 minutes, and the amplification products were successfully visualized by LFD strips. The analytical sensitivity of LAMP-LFD was determined using 10-fold serial dilutions of E. granulosus DNA. The minimal concentration detected was 10 fg/ μ l, and no cross-reactivity was observed with DNA extracted from Taenia solium, Taenia saginata, and Fasciola hepatica . The ability of the developed LAMP-LFD assay to detect cystic echinococcosis was further evaluated with 62 cyst samples from slaughtered cattle in Juja Abattoir, Kiambu County, Kenya. The LAMP-LFD was able to detect 59/62 (95.2%, 95% CI 0.87–0.98) as positive samples of E. granulosus compared to 53/62 (85.5%, 95% CI 0.75–0.92) by nested PCR assay. Conclusion . Our results indicated that the developed LAMP-LFD technique was more sensitive than the nested PCR assay, rapid, and easy to perform with a simple visual detection of products. Therefore, it could be an important point-of-care diagnostic tool for cystic echinococcosis.